2017
DOI: 10.3389/fphar.2017.00549
|View full text |Cite
|
Sign up to set email alerts
|

A Pilot Study Evaluating the Safety of Intravenously Administered Human Amnion Epithelial Cells for the Treatment of Hepatic Fibrosis

Abstract: Liver cirrhosis is the 6th leading cause of death in adults aged 15–59 years in high-income countries. For many who progress to cirrhosis, the only prospect for survival is liver transplantation. While there is some indication that mesenchymal stem cells may be useful in reversing established liver fibrosis, there are limitations to their widespread use – namely their rarity, the need for extensive serial passaging and the associated potential for genomic instability and cellular senescence. To this end, we pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(38 citation statements)
references
References 32 publications
(34 reference statements)
0
37
0
1
Order By: Relevance
“…The same could be applied to pirfenidone for the treatment of pulmonary fibrosis, as pirfenidone primarily targets interstitial fibrosis ( Figure 3b) and can also be associated with several side effects when therapeutically administered (Jiang et al, 2012). As AECs (Lim, Hodge, Moore, Wallace, & Sievert, 2017), exosomes (ClinicalTrials.gov Identifier NCT02138331; NCT03384433), and serelaxin (Teerlink et al, 2013) have separately been evaluated in clinical trials, novel strategies incorporating this combination therapy can be fast-tracked for human trials.…”
Section: Discussionmentioning
confidence: 99%
“…The same could be applied to pirfenidone for the treatment of pulmonary fibrosis, as pirfenidone primarily targets interstitial fibrosis ( Figure 3b) and can also be associated with several side effects when therapeutically administered (Jiang et al, 2012). As AECs (Lim, Hodge, Moore, Wallace, & Sievert, 2017), exosomes (ClinicalTrials.gov Identifier NCT02138331; NCT03384433), and serelaxin (Teerlink et al, 2013) have separately been evaluated in clinical trials, novel strategies incorporating this combination therapy can be fast-tracked for human trials.…”
Section: Discussionmentioning
confidence: 99%
“…No severe adverse events were found to be associated with hAEC treatment. A Phase 1 trial of hAECs in adults with compensated cirrhosis is also underway in our institution ( 21 ) (ACTRN12616000437460).…”
Section: Discussionmentioning
confidence: 99%
“…The Cell Therapies and Regenerative Medicine Platform (CTRMP) at the Monash Health Translation Precinct has a cryobank of isolated, screened, and stored hAECs for clinical trial use ( 21 ). These cells are routinely obtained from healthy women with a healthy singleton pregnancy undergoing an elective cesarean section at term and donating their placenta for clinical trial purposes with informed consent.…”
Section: Methodsmentioning
confidence: 99%
“…It is uncertain, if the changes induced in the cell genome would not cause further spontaneous mutations leading to cancer. However, such concerns are not raised by the use of amnion epithelial cells [11] and, as it can be assumed, HLC obtained from them. Preclinical studies on mice [14,113] using HLC obtained from hAEC have shown, that their use in the treatment of liver failure in humans does not require the use of immunosuppressive treatment [13].…”
Section: Differentiation Of Amniotic Epithelial Cellsmentioning
confidence: 99%
“…placenta and umbilical cord are abundant sources of cells, that meet the biological criteria of good transplantable material, and can be isolated in a manner that does not raise moral and ethical controversies. Some of afterbirth cell populations are successfully used in clinical trials, including the treatment of type 1 diabetes, systemic lupus erythematosus and ischemic stroke [6][7][8][9][10][11]. Both in vivo and in vitro studies have shown that cells derived from these sources, e.g.…”
Section: Introductionmentioning
confidence: 99%